Gender, Discrimination, and Housing in Turn of the Century Montréal: What Mapping the Census Returns of Immigrants Can Tell Us - Sweeny, Robert C. H. (Frontiers in Digital Humanities, 2016)
Women owned a quarter of all rental units in Montréal, QC, Canada, in 1903, a city where 85% of the population were tenants. In no major city in the world today, do women control an equivalent area of the formal economy. This paper asks did the gender of proprietorship matter? It answers this through a series of tests linking a 30% sample of all immigrant-headed households in the 1901 census with a complete historical GIS of all properties and their owners in the city for 1903. The paper plays special attention to Ashkenazi Jews, Syrians, Chinese, and Italians, as these relatively recent immigrants constituted a major break with the largely British and French ancestry of the majority of the population in this 300-year-old settler colony. It then links the patterns in the sample to an index of all households in the census, to explore how these immigrant families integrated into the larger host communities. The paper shows that landladies and landlords had differing practices with regard to overcrowding and to the enforcement of segregation. The paper makes a sustained argument for rethinking how we should approach the relationship between gender and property.